Measurement of Success in The Integrated Prescribing Information System at Ananda Bekasi Hospital - Ferdi Novalendo; Rizal Syarief; Arif Imam Suroso (School of Business, IPB University (SB-IPB), 2018)
Electronic prescribing is highly useful for hospitals to reduce the error level of prescribing medicine to patients. Currently, a large number of prescribing errors are made by doctors to patients; however, there are also patients who are disobedient to prescriptions made by doctors. This research aims to evaluate whether the prescription information system at Ananda Bekasi Hospital can be evaluated to be successful and has a positive impact on the performance of doctors to patients. The study was conducted on the success of integrated prescribing information system at Ananda Bekasi Hospital using the theoretical framework of DeLone & McLean’s information system model. Data processing was conductedby using SEM-PLS method. Aspects of technology analyzed in determining prescription information systems include system quality, information quality, service quality, usage intention, user satisfaction, and net benefits. Referring to the technological aspects, the research results on prescribing information system are as follow: information quality influences the usage intention and user satisfaction, and usage intention and user satisfaction influence the net/benefit. Hence, the results of the research show that the information system success model of DeLone and McLean is not fully proven empirically to be successful in the prescibing information system in Ananda Bekasi Hospital.Keywords: DeLone & McLean, Information System Success, user satisfaction, prescribing information systems, SEM-PLS